Pelatihan Penggunaan Microlearning Dengan Powtoon Dalam Pembelajaran Untuk Meningkatkan Kompetensi Pedagogik Guru - Yuliatun, Tutik; Uskenat, Kristina (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
The use of technology for the implementation of learning is increasingly being used. One of them is by making learning videos. Community service activities are carried out through training on the use of microlearning with powtoons in learning. This training activity aims to improve teacher pedagogic competence. The targets in this training activity are Muhammadiyah Kartosentanan Middle School teachers which will be held in September 2022 to October 2022. This training activity is carried out in five stages including surveys and permits; socialization; training; monitoring; and evaluation. The results obtained were in the form of increasing teacher pedagogical competence through training in the use of microlearning with powtoons in learning. The increase in teacher competency can be seen from the average pretest and posttest results where 92% of teachers already know about the use of microlearning in learning.